Depressive symptoms and receipt of pensions: a cross-sectional analysis of the ELSI-Brazil study - Ana Paula Goulart de Freitas; Klaide Lopes de Sena; Jôsi Fernandes de Castro Rodrigues (Epidemiologia e Serviços de Saúde, 2023)
ABSTRACT Objective To investigate association between depressive symptoms and receipt of retirement pensions or other pensions in the Brazilian population aged 50 years or older. Method This was a cross-sectional study with participants from the baseline (2015-2016) of the Longitudinal Study of the Health of Elderly Brazilians. Depressive symptoms were measured by the eight-item Center for Epidemiologic Studies Depression Scale. Prevalence ratios (PR) were obtained by Poisson regression. Results Among the total 8,469 participants, 33.9% (95%CI 32.8;34.9) reported depressive symptoms and 52.8% (95%CI 51.8;53.9) of the participants received a retirement or other pension. Prevalence of depressive symptoms was lower among participants receiving a retirement or other pension (PR = 0.79; 95%CI 0.73;0.86). Association remained significant after adjustments for sociodemographic and health indicators (PR = 0.84; 95%CI 0.76;0.92). Conclusion Participants who receive retirement or other pensions are less likely to report depressive symptoms.